2021
DOI: 10.1177/21501327211040746
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Determinants of COVID-19 Vaccine Hesitancy, Fear of Infection, and Protection Self-Efficacy

Abstract: Objectives: Arkansas COVID-19 vaccine uptake has been lower than the national average. This study examined associations between sociodemographic factors and COVID-19 vaccine hesitancy, fear of infection, and protection self-efficacy. Methods: Adults either residing, having employment, or receiving health care in Arkansas (n = 754) participated in an online survey between October 30, 2020 and January 16, 2021. Participants were recruited in both rural and urban areas from 6 Arkansas primary care clinics. Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
6
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 17 publications
(19 reference statements)
9
69
6
4
Order By: Relevance
“…The present study found that people with high levels of fear of COVID-19 at waves 1 and 3 were more likely to be willing to receive a vaccine at wave 3. This finding is consistent with most studies that addressed this issue [ 15 , 22 , 26 , 27 , 41 , 46 48 , 54 ]. A typical characteristic of fear is that people tend to avoid what they fear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found that people with high levels of fear of COVID-19 at waves 1 and 3 were more likely to be willing to receive a vaccine at wave 3. This finding is consistent with most studies that addressed this issue [ 15 , 22 , 26 , 27 , 41 , 46 48 , 54 ]. A typical characteristic of fear is that people tend to avoid what they fear.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding fear of COVID-19, several studies have already explored the association between fear of COVID-19 and vaccine hesitancy [ 15 , 22 , 26 , 27 , 41 , 46 48 ]. All of them except one [ 46 ] found that fear of COVID-19 was positively associated with willingness to be vaccinated against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Variables in the symbol column correspond to Equation 1 . INDEX DOMAIN INDICATOR SOURCE LEVEL SYMBOL NOTES REFERENCES SEVI 1 Jobseekers Allowance Rate NOMIS 1 MSOA v 1 6 , 11 , 12 1 Rank of Index of Multiple Deprivation (IMD) Gov.uk 2 LSOA v 2 Averaged over LSOAs within MSOA 6 , 12 , 13 , 14 , 15 1 Long term unemployment, per 100 population of working age† PHE Fingertips 6 MSOA v 3 6 , 11 , 12 , 16 2 Proportion population over 65 ONS 4 MSOA v 4 17 , 18 2 Ethnicity (% non-white population) * NOMIS 1 MSOA v 5 5 , 19 , 20 2 Household overcrowding* Gov.uk 2 LSOA v 6 Averaged over LSOAs within each MSOA 2 , 6 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…These are similar to those characteristics found to be associated with vaccine hesitancy in other works from the UK and further afield. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…These are similar to those characteristics found to be associated with vaccine hesitancy in other works from the UK and further afield. 10,11 Avoiding unchecked viral spread is important for reasons beyond the obvious need to safeguard life. COVID-19 infection comes with at least two additional major risks; the risk of inducing 'Long COVID' in a substantial proportion of patients, 12 and the risk of allowing yet more virulent or transmissible variants to emerge which may evade the current vaccines.…”
Section: Introductionmentioning
confidence: 99%